Longitudinal change in parent postsecondary expectations for youth with disabilities. Issue 20 (25th September 2021) - Kirby, Anne V.; Holmes, Laura Graham; Persch, Andrew C.
Abstract: Purpose: Expectations held by parents of youth with disabilities contribute to decision making and planning for adulthood. This study investigated longitudinal stability of parent expectations about the transition to adulthood for youth with disabilities (i.e., likelihood of obtaining postsecondary education, living independently, becoming financially self-sufficient) and how the stability of parent expectations was related to adult outcomes. Materials and methods: Participants were parents of 3640 youth who participated in the National Longitudinal Transition Study-2 (NLTS2) waves 1 and 2 and had available data related to parent expectations. Results: Parent expectations were moderately correlated across waves; however, over one-third of parents changed their expectations across waves, including directional shifts (e.g., changing from thinking they probably will achieve the outcome to probably will not achieve it). Directional shifts in parent expectations between waves 1 and 2 significantly predicted young adult outcomes at wave 5. The children of parents who demonstrated uncertainty, as indicated by directional expectation shifts, were less likely live independently as young adults. Family involvement in the transition process is critical and should continue to be advocated for in both policy and practice. Improved supports may be warranted for families who experience uncertainty. Implications for rehabilitation: Practitioners should recognize that parents of youth with disabilities have expectations for their child's transition to adulthood that may change over time and are influenced by factors such as youth age, disability classification, gender, and socioeconomic status. The ways parents' expectations change over time may have lasting implications for their child; specifically, we identified that youth of parents who change their expectations negatively (by shifting to expect less independence) are less likely to attain certain adult milestones. Parents experiencing uncertainty about their youths' postsecondary potential may require additional support and resources to understand their child's strengths and challenges, consider available services, and ultimately to promote more independent outcomes for the youth.